2023
DOI: 10.1097/qai.0000000000003153
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Reduction in Chemsex Practice in Men Who Have Sex With Men During COVID-19 Lockdown? Results of the CheRRLock Study

Abstract: a,c on behalf of the "190" working group Background and aims: Chemsex is a growing concern among men who have sex with men (MSM). COVID-19 lockdowns have had consequences on social and sexual interactions. We aimed to assess changes in chemsex practices during COVID-19 lockdown in France among MSM and factors associated with maintaining or increasing chemsex practice.Methods: Repeated face-to-face questionnaires were conducted at "Le 190" Sexual Health Center, Paris, France, exploring lifestyle, sexual, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…loneliness, loss of sense of meaning), and reduced access to health care. 7 This may partially explain that a majority expressed a need for the intervention. Data was collected retrospectively and was self-reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…loneliness, loss of sense of meaning), and reduced access to health care. 7 This may partially explain that a majority expressed a need for the intervention. Data was collected retrospectively and was self-reported.…”
Section: Discussionmentioning
confidence: 99%
“…5 While synthetic substances such as crystal methamphetamine (or crystal meth), g-hydroxybutyrate/gammabutyrolactone (GHB/GBL), and cathinones (including 3-methylmethcathinone/3-chloromethcathinone (3MMC/ 3CMC), mephedrone, etc. ), and also cocaine and ketamine 6,7 are mainly used in chemsex, the term includes several practices that vary in terms of consumed substances, intensity, frequency, and nature. For instance, 'Slam' is a type of chemsex practice involving the injection of drugs reported among about 5% of people practising chemsex in literature reviews.…”
Section: Introductionmentioning
confidence: 99%
“…47 A French study of chemsex behaviour during lockdown found that 64% of participants maintained (22%) or increased (42%) while 36% stopped (14%) or decreased (22%) their chemsex drug consumption during lockdown. 48 They also found that the median number of chemsex days during 6 weeks of lockdown (n = 8) increased significantly from the 6 weeks preceding lockdown (n = 3). 48 The prevalence of GHB/GBL use (52% vs 58%, P = 0.038) and slamming (19% vs 24%) both increased though the latter was not statistically significant.…”
Section: Increased or Unchanged Sdu Prevalence Or Frequencymentioning
confidence: 91%
“…48 They also found that the median number of chemsex days during 6 weeks of lockdown (n = 8) increased significantly from the 6 weeks preceding lockdown (n = 3). 48 The prevalence of GHB/GBL use (52% vs 58%, P = 0.038) and slamming (19% vs 24%) both increased though the latter was not statistically significant. 48 Across three waves of follow-up, corresponding to three episodes of pandemic-related restrictions, between 40.4% and 46.9% of a PrEP-using cohort reported chemsex participation.…”
Section: Increased or Unchanged Sdu Prevalence Or Frequencymentioning
confidence: 91%
“…8,9 There has been an exponential increase in the association between the practice of chemsex and the population of men who have sex with men (MSM) in both developed and developing countries. [10][11][12][13] There are a series of health risks associated with this practice, particularly vulnerability to sexually transmitted infections, including HIV. Two literature reviews confirm evidence of the association between chemsex and increased risk of HIV infection among MSM 14,15 due to susceptibility to engage in sexual practice that increase HIV risk that include barebacking, having multiple casual/occasional partners, group sex, challenging/complex sexual engagement (i.e.…”
Section: Introductionmentioning
confidence: 99%